Security and Market Liquidity Enhanced Transactive Energy System for Residential End Users - Vanga Anil; S. L. Arun (IEEE Access)
The swift progress of economically viable sustainable energy resources, coupled with advancements in communication and computational technologies, has facilitated the introduction of the Transactive Energy System (TES) within the smart grid. However, TES is facing critical challenges in security and economics. Security concerns include data integrity, authentication, confidentiality, scalability, and privacy, while economic challenges involve penalty reduction and market liquidity. In order to address these issues, this study proposes an integrated approach combining elliptic curve digital signatures with hash functions for data integrity and authentication, Paillier cryptography for confidentiality, and calibrated noise for privacy preservation. Further, scalability is achieved through an intelligent grouping mechanism, while market liquidity is enhanced using a demand-supply weighting strategy and a demand response approach based on locality net demand. Moreover, case studies were conducted to assess the effectiveness of the proposed approach, resulting in average electricity bill savings of 12.29%, improvements in privacy protection of 41.07%, and an enhancement in computing scalability of 44.79%. These results validate the proposed framework as a secure, scalable, and economically viable solution for TES.